Brown Planthopper Egg Parasitization in Rice Fields with Different Growth Ages - Yurista Sulistyawati; Y. Andi Trisyono; Witjaksono Witjaksono (Universitas Gadjah Mada, 2022)
The brown planthopper, Nilaparvata lugens Stål. (Hemiptera: Delphacidae), is one of the most important pests attacking rice plants. One of the strategies to control this pest is by using natural enemies, including egg parasitoids. This study aimed to investigate the species of N. lugens egg parasitoids and their parasitism levels in one rice ecosystem with different growth stages. The research was conducted by selecting three rice plots aged 3, 6, and 10 weeks after planting. Potted rice plants with N. lugens eggs were placed in those rice plots for two days and recollected for observations. The same release was repeated 3 weeks later at the same rice plots in the same site. Egg parasitoids of N. lugens found during this study were Oligosita sp. and Anagrus sp. The highest number of egg parasitoids were found at the rice plants aged 6 weeks after planting with 14.50 and 13.50 individuals collected during first and second trapping, respectively. In addition, the level of parasitism ranged from 6.89-22.26% with the highest parasitism was occurred in the 6-week old rice. These findings may suggest that different rice planting dates may benefit the egg parasitoids of N. lugens which could reduce the risk of outbreaks.